UNDERSTANDING AND ADDRESSING CHILD ABUSE: CASE STUDY OF B40 COMMUNITY - Norsuhaily Abu Baka; Mohammad Shaban Alsmadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The issue of child abuse has never gone away from the social problems existed in Malaysia since a long a time ago. The factors of child abuse cases are common in families with low economic status. Therefore, this study aimed to look at the most significant relationship factors, the most influential factors and the public’s view of the efforts and measures taken to prevent child abuse among B40 community. The researcher had identified four factors, namely economic factors, lack of religious knowledge, household breakdown factors and parental stress at workplaces. The research methodology used in this study was a mixed qualitative and quantitative method with a total of 63 respondents. The instrument of the study was through a questionnaire form distributed to the study sample around Gong Badak, Kuala Nerus and the sample of the study within UniSZA (Sultan Zainal Abidin University). The results of the survey data were analyzed using SPSS software, Statistical Package for Social Science version 23. For this study, the researcher used descriptive analysis to analyze the frequency and percentage of respondents while infrared analysis on correlation and regression tests to see the relationship and influence of the variables. The overall results of this study showed that the lack of religious knowledge had the strongest degree of relationship and influence followed by economic pressure factor that both results in sig. p <0.05 contributing to the prevalence of child abuse according to perceptions among B40 community. For the open-ended question, most of the respondents encouraged each member of the community to study religious science more thoroughly and to understand the essence of what Islam teaches in the context of building a successful family while maintaining good relations with each other, especially parent-child relationships. Overall, the results of this study showed that people are beginning to realize the importance of understanding and practicing the teachings of Islam in their daily lives in order to enjoy a happy, secure, and prosperous family life.